THE IMPLEMENTATION OF INTERACTIVE MULTIMEDIA TO IMPROVE LEARNING OUTCOMES IN FRACTION AT PRIMARY SCHOOL - Mahdalena, Mahdalena (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2020)
The study was a classroom action research conducted at SDN 41 Sungai Ambawang, located on Jalan Sambas Timur Perumnas IV Sungai, Kubu Raya Regency, in IV grade with a total of 30 students. The formulation of the problems in this study are: (1) How is the planning of learning using interactive multimedia on fraction material in IV grade SDN 41 Sungai Ambawang; (2) How is the implementation of learning using interactive multimedia on fraction material in IV grade SDN 41 Sungai Ambawang; (3) What are the learning outcomes of students after using interactive multimedia on fractions material in IV grade SDN 41 Sungai Ambawang. Data collection techniques in this study used tests, interviews, observation, and documentation. While the data analysis technique used analysis and reflection in each cycle, based on data and results of observations, analysis, and reflection carried out by educators as researchers. In learning planning using interactive multimedia on fraction in IV grade at SDN 41 Sungai Ambawang has been done well. It can be seen from the scores obtained in the preparation of RPP, each component has increased. In Cycle I, an average score of 72.05% increased in Cycle II to 88.9%, with an increase of 16.85% difference. The implementation of learning using interactive multimedia on fraction in IV grade at SDN 41 Sungai Ambawang, based on the results of colleagues' observations, that the implementation of learning using interactive multimedia has been appropriately implemented as expected. It can be seen from the assessment of teacher activity in the first cycle an average of 67.5% was obtained, then an increase in the second cycle to 92.5%, an increase of 25%.